Brain Under Fatigue – Can Perceived Fatigability in Multiple Sclerosis Be Seen on the Level of Functional Brain Network Architecture? - Sobczak, Anna Maria; Bohaterewicz, Bartosz; Ceglarek, Anna; Zyrkowska, Aleksandra; Fafrowicz, Magdalena; Slowik, Agnieszka; Wnuk, Marcin; Marona, Monika; Nowak, Klaudia; Zur-Wyrozumska, Kamila; Marek, Tadeusz (Frontiers in Human Neuroscience, 2022)
Background: Fatigue is one of the most common symptoms of multiple sclerosis (MS), significantly affecting the functioning of the patients. However, the neural underpinnings of physical and mental fatigue in MS are still vague. The aim of our study was to investigate the functional architecture of resting-state networks associated with fatigue in patients with multiple sclerosis. Methods: The sum of 107 high-functioning patients underwent a resting-state scanning session and filled out the 9-item Fatigue Severity Scale. Based on the FSS score, we identified patients with different levels of fatigue using the cluster analysis. The low-fatigue group consisted of n=53 subjects, while the high-fatigue group n=48. The neuroimaging data were analyzed in terms of Functional Connectivity between various resting-state networks as well as Amplitude of Low-Frequency Fluctuation and Fractional ALFF. Results: Two-sample t-test revealed between-group differences in FC of posterior Salience Network. No differences occurred in Default Mode Network and Sensorimotor Network. Moreover, differences in fALFF were shown in the right middle frontal gyrus and right superior frontal gyrus, however, no ALFF differences took place. Conclusions: Current study revealed significant functional network architecture between-group differences associated with fatigue. Present results suggest the higher level of fatigue is related to deficits in awareness as well as higher interoceptive awareness and nociception.